Effects of Noisy Galvanic Vestibular Stimulation During a Bimanual Tracking Robotic Task - Valdés, Bulmaro A.; Menon, Carlo (Frontiers in Neuroscience, 2019)
Background: Noisy galvanic vestibular stimulation (nGVS) has been shown to improve motor performance in people with and without disabilities. Previous investigations on the use of nGVS to improve upper-limb motor performance have focused on unimanual fine motor movements, nevertheless, bimanual gross movements are also essential for conducting activities of daily living and can be affected as a result of cerebral dysfunction. Consequently, in this study we investigated the effects of nGVS on bimanual gross motor performance. Methods: 12 healthy participants completed a visuomotor task in which they performed bimanual upper-limb movements using two robots. During the task, participants tracked a target that oscillated following a sinusoidal amplitude-modulated trajectory. In half of the trials, participants received subthreshold nGVS, in the other half, they received sham stimulation. Primary outcome measure: percent improvement in root mean square error (RMSE) between the target’s and cursors’ trajectories. Secondary outcome measures: percent improvement in lag between the cursors and target; and percent improvement in RMSE between the cursors’ trajectories. A post-test questionnaire was administered to evaluate the experience of participants. Results: Tracking error was not affected by nGVS: left -2.6(5.5)%, p=0.128; right -0.9(6.2)%, p=0.639; nor was bimanual coordination -1.5(9.6)%, p=0.590. When comparing if one hand was affected more than the other, we did not find a statistically significant difference (-1.7(3.3)%, p=0.098). Similar results were found for the lag. Questionnaire results indicated that the robotic devices did not limit participants’ movements, did not make participants feel unsafe, nor were they difficult to control. Furthermore, participants did not feel unsafe with the nGVS device, nor did they report any discomfort due to nGVS. Conclusions: Results suggest that nGVS applied to people without disabilities do not affect bimanual gross motor performance. However, as this was the first study to investigate such effects, stimulation parameters were based on previous unimanual fine motor studies. Future studies should investigate optimal stimulation parameters for improving upper-limb gross motor performance. Overall, participants felt safe using the robotic devices and receiving the noisy electrical stimulation. As such, a similar setup could potentially be employed for subsequent studies investigating the relation between upper-limb performance and nGVS.